2008
DOI: 10.1111/j.1399-3089.2008.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of double negative T regulatory cells induces B‐cell death in vivo and alters rejection pattern of rat‐to‐mouse heart transplantation

Abstract: This study suggests that adoptive transfer of xenoreactive DN-Treg cells can inhibit B-cell responses in vivo. DN-Treg cells may be valuable in controlling B-cell responses in xenotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…Mice were monitored for the development of diabetes by measuring blood glucose levels twice weekly. In the event of new-onset diabetes, DN T cells (4×10 6 ) were transferred to the new-onset diabetic NOD mice, and blood glucose levels were followed up every other day following adoptive transfer. In an islet allograft model, GAD65 peptide-primed DN T cells (5×10 6 ) were injected into new-onset diabetic NOD mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were monitored for the development of diabetes by measuring blood glucose levels twice weekly. In the event of new-onset diabetes, DN T cells (4×10 6 ) were transferred to the new-onset diabetic NOD mice, and blood glucose levels were followed up every other day following adoptive transfer. In an islet allograft model, GAD65 peptide-primed DN T cells (5×10 6 ) were injected into new-onset diabetic NOD mice.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, DN T cells (2×10 6 ) were transferred to 5-week-old female NOD mice. Mice were monitored for the development of diabetes by measuring blood glucose levels twice weekly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they are able to induce tolerance by repressing CD4 In addition, there are CD4 negative and CD8 negative (CD4 K and CD8 K ), thus DN Tregs that promote the development of tolerance (Strober et al 1996). This cell population has been identified in xenotransplant models (Chen et al 2003, Ma et al 2008. On the basis of animal studies, it has been shown that DN cells show only limited suppressive function in naïve mice, while DN Tregs are strongly suppressive in xenograft recipients and induce tolerance to such extent that organ rejection is prevented (Strober et al 1996, Chen et al 2003, Ma et al 2008, Juvet & Zhang 2012.…”
Section: Tumor Infiltrating Lymphocytes and Cancer Progressionmentioning
confidence: 99%
“…This cell population has been identified in xenotransplant models (Chen et al 2003, Ma et al 2008. On the basis of animal studies, it has been shown that DN cells show only limited suppressive function in naïve mice, while DN Tregs are strongly suppressive in xenograft recipients and induce tolerance to such extent that organ rejection is prevented (Strober et al 1996, Chen et al 2003, Ma et al 2008, Juvet & Zhang 2012. Similarly, tumors develop strategies to escape cytotoxic T cells and are able to induce a micromilieu that inhibits the anti-neoplastic function of effector T cells and memory CD8 C T cells.…”
Section: Tumor Infiltrating Lymphocytes and Cancer Progressionmentioning
confidence: 99%